Significance of universal methodology for assessing borrower's creditivity - O. I. Ditsulenko; E. A. Posnaya; N. V. Yurchenko; E. Yu. Cherkashina (Вестник Северо-Кавказского федерального университета)
Introduction. One of the main problems in the activities of commercial banks is the risk of non-repayment of loans, as a result of which the amount of banking profit decreases and the risk of bankruptcy arises.Goal. The purpose of the study is to prove the need and importance of developing and implementing an assessment of the borrower’s creditworthiness to reduce the risk of non-repayment of issued loans.Materials and methods. Every year, the Bank of Russia expands its review of lending statistics to improve the information support of users with statistical data. In this regard, the development and implementation of a universal methodology for assessing the borrower’s creditworthiness is becoming increasingly important. Newly published reports suggest that corporate lending is growing progressively, becoming the main driver of bank income growth. In 2022 alone, the total corporate loan portfolio of Russian banks amounted to 59.1 trillion rubles, while the portfolio of unsecured loans in the consumer segment approached the figure of 12 trillion rubles. The study shows that the volume of loans issued to legal entities and individual entrepreneurs occupies the largest share among all segments of the credit market.Results and discussion. Consequently, an important problem of the modern financial system is the development and implementation of a thorough and universal methodology for assessing the creditworthiness of borrowers in order to reduce the existing risks of non-repayment. The article analyzes existing methods for assessing the borrower's creditworthiness and draws conclusions regarding the possibility of developing and implementing a universal model for assessing the borrower's creditworthiness and the effect of its implementation.Conclusion. As a result of the development and implementation of a universal methodology for assessing the borrower’s creditworthiness, the risk of non-repayment of loan funds will be significantly reduced, since the data that will be used in the calculation will reflect the real financial condition of the potential borrower.